2021
DOI: 10.1073/pnas.2023613118
|View full text |Cite
|
Sign up to set email alerts
|

The synaptonemal complex imposes crossover interference and heterochiasmy inArabidopsis

Abstract: Meiotic crossovers (COs) have intriguing patterning properties, including CO interference, the tendency of COs to be well-spaced along chromosomes, and heterochiasmy, the marked difference in male and female CO rates. During meiosis, transverse filaments transiently associate the axes of homologous chromosomes, a process called synapsis that is essential for CO formation in many eukaryotes. Here, we describe the spatial organization of the transverse filaments in Arabidopsis (ZYP1) and show it to be evolutiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

33
243
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 152 publications
(277 citation statements)
references
References 104 publications
33
243
1
Order By: Relevance
“…For instance, in barley it was reported that dramatic reduction of normal levels of ZYP1 by RNAi also drastically reduce CO formation (Barakate et al, 2014). However, in the case of Arabidopsis and rice a malfunctioning SC does not affect recombination and may even increase CO frequency and abolish CO interference (Wang et al, 2010;Capilla-Perez et al, 2021;France et al, 2021). In both holocentric Rhynchospora and Luzula it was shown that they apparently have conserved SC structures as immunostaining with SC proteins showed the conserved pattern for monocentric species (Cabral et al, 2014;Heckmann et al, 2014).…”
Section: Meiotic Recombination In Holocentric Plantsmentioning
confidence: 99%
“…For instance, in barley it was reported that dramatic reduction of normal levels of ZYP1 by RNAi also drastically reduce CO formation (Barakate et al, 2014). However, in the case of Arabidopsis and rice a malfunctioning SC does not affect recombination and may even increase CO frequency and abolish CO interference (Wang et al, 2010;Capilla-Perez et al, 2021;France et al, 2021). In both holocentric Rhynchospora and Luzula it was shown that they apparently have conserved SC structures as immunostaining with SC proteins showed the conserved pattern for monocentric species (Cabral et al, 2014;Heckmann et al, 2014).…”
Section: Meiotic Recombination In Holocentric Plantsmentioning
confidence: 99%
“…proteins one important caveat needs to be taken into consideration: the measurements could yield deviating results depending on the primary antibody used for the analysis. This is because each primary antibody might recognize different epitopes of the same protein, and this can be resolved at a resolution of 30 nm, as shown in a recent publication (Capilla-Perez et al, 2021). Furthermore, an additional variation is added to the measurements if the combination of primary and secondary antibodies, which is roughly 30 nm long, is taken into account.…”
Section: Meiotic Repair Proteins and Colocalization Of Complex Partnersmentioning
confidence: 99%
“…COs are formed in the context of the meiotic axes and the synaptonemal complex (SC) and physically link homologous chromosomes to enable correct segregation. The SC is a protein structure that builds on the axes, tightly connects homologous chromosomes and is required for inter-homolog recombination and interference ( Zickler and Kleckner, 1999 ; Kleckner, 2006 ; Mercier et al, 2015 ; Smith and Nambiar, 2020 ; Capilla-Perez et al, 2021 ; France et al, 2021 ). The repair of the residual breaks yields NCO products, possibly via synthesis-dependent strand-annealing, intersister recombination, or non-homologous end-joining ( Higgins et al, 2004 ; Chen et al, 2008 ; Mancera et al, 2008 ; Sims et al, 2019 ).…”
Section: Meiosismentioning
confidence: 99%
See 2 more Smart Citations